1998
DOI: 10.2134/agronj1998.00021962009000030007x
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Leaf Morphology and Defoliation Tolerance

Abstract: Plant tolerance to pest injury is an ideal component of integrated pest management (IPM) programs, because it places no selection pressure on pest populations, but tolerance is little understood and its use in pest management is limited. In field experiments in 1994, 1995, and 1996, we characterized tolerance to defoliation in ‘Clark’ soybean [Glycine max (L.) Merr.] isolines differing in leaf morphology: 3‐ and 5‐leaflet, narrow and wide leaflet. Sequential defoliation was imposed manually at the R2 stage (fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 27 publications
4
35
0
1
Order By: Relevance
“…The high leaf area index values were likely due to adequate rainfall that season, allowing plants to better compensate for leaf area loss through leaf regrowth. Haile et al (1998) reported similar postdefoliation soybean leaf regrowth in seasons with ample rainfall. A relationship between leaf area index and yield was not expected in these data sets; plateau levels (with zero slope) had been achieved.…”
Section: Resultsmentioning
confidence: 73%
“…The high leaf area index values were likely due to adequate rainfall that season, allowing plants to better compensate for leaf area loss through leaf regrowth. Haile et al (1998) reported similar postdefoliation soybean leaf regrowth in seasons with ample rainfall. A relationship between leaf area index and yield was not expected in these data sets; plateau levels (with zero slope) had been achieved.…”
Section: Resultsmentioning
confidence: 73%
“…Plants that grow indeterminately can better compensate for tissue loss (Haile et al 1998). In fact, indeterminately growing trees may be less susceptible to early season defoliation because they can continue to grow throughout the summer and compensate for lost tissue.…”
Section: Ecological Implicationsmentioning
confidence: 99%
“…Insetos-praga desfolhadores atuam modificando a arquitetura do dossel, reduzindo a área foliar efetiva, diminuindo a intercepção da luz, a taxa de crescimento da cultura (TCC), o acúmulo de massa seca (MS) e, conseqüentemente, levando ao decréscimo do rendimento de grãos (HAILE et al, 1998b;GAZZONI & MOSCARDI, 1998).…”
Section: Introductionunclassified